PEMBERDAYAAN MASYARAKAT KORBAN BENCANA BANJIR DI KOTA MANADO - MASIKOME, JUNIOR HERMAN JOHANES; LENGKONG, FLORENCE DAICY; LONDA, VERY (JURNAL ADMINISTRASI PUBLIK, 2018)
government provides a disaster program to prepare citizens, especially those who live indisaster-prone areas to be able to be ready and alert to natural disasters that can occur at any time.Article 26 of Law No. 24 of 2007 concerning disaster management explains that the community has theright to obtain education, training, and skills in implementing disaster management, because Indonesiahas a high risk of natural disasters including the city of Manado. In community empowerment, ingeneral it can be interpreted as a process that builds people or society through developing communitycapacity, changing community behavior, and organizing the community. The purpose of empowermentfor the community is to provide opportunities for development and development of living welfare, thecreation of independence in building a decent and sufficient life for citizens with a developing economiclife. Especially the flood disaster in Manado City is classified as a high category so that based on theresults of disasters that always exist every year and central BPBD and BNPB coordination meetings,Manado City receives training and mentoring programs for the Tangguh village program from theManado BPBD in accordance with the village disaster resilient theme for the year 2017 is a flood.Kata Kunci: Pemberdayaan Masyarakat, Korban, Bencana Banjir